2001
DOI: 10.1093/oxfordjournals.molbev.a003956
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Identification of Wild and Domestic Cats (Felis silvestris) and Their Hybrids Using Bayesian Clustering Methods

Abstract: Crossbreeding with free-ranging domestic cats is supposed to threaten the genetic integrity of wildcat populations in Europe, although the diagnostic markers to identify "pure" or "admixed" wildcats have never been clearly defined. Here we use mitochondrial (mt) DNA sequences and allelic variation at 12 microsatellite loci to genotype 128 wild and domestic cats sampled in Italy which were preclassified into three separate groups: European wildcats (Felis silvestris silvestris), Sardinian wildcats (Felis silves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
174
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(193 citation statements)
references
References 40 publications
12
174
0
2
Order By: Relevance
“…The identification of each individual as F. s. silvestris was based on external coat pattern, and other morphologic characteristics, including intestine and cranial indexes (Ragni and Possenti 1996). The identity of some wildcats that showed physical patterns compatible with hybrids with domestic cats was confirmed by genetic analysis using autosomal microsatellite markers (Randi et al 2001). …”
Section: Animalsmentioning
confidence: 99%
“…The identification of each individual as F. s. silvestris was based on external coat pattern, and other morphologic characteristics, including intestine and cranial indexes (Ragni and Possenti 1996). The identity of some wildcats that showed physical patterns compatible with hybrids with domestic cats was confirmed by genetic analysis using autosomal microsatellite markers (Randi et al 2001). …”
Section: Animalsmentioning
confidence: 99%
“…Previous studies clearly show that the development of more powerful tools is still critical to accurately identify parental and hybrid individuals of this species because of the high similarity in morphology and genomes of wild and domestic forms. Although microsatellites have been the dominant markers in wildcat genetic studies (for example, Beaumont et al, 2001;Randi et al, 2001;Pierpaoli et al, 2003;Lecis et al, 2006;Germain et al, 2008;Eckert et al, 2010;O'Brien et al, 2009), and recently mtDNA diagnostic SNPs have been suggested (Driscoll et al, 2011), the increasing availability and numerous advantages of nuclear SNPs make them an appealing alternative and/or a complement to maternal and paternal lineage markers. SNPs have been attracting a growing interest in a wide range of evolutionary applications and are becoming efficient tools among wildlife conservation-oriented studies (Brumfield et al, 2003;Morin et al, 2004;Seddon et al, 2005;Morin et al, 2009).…”
Section: Snp Simulations For Admixture Analysismentioning
confidence: 99%
“…The survival and conservation of indigenous populations of the European wildcat might be locally threatened by introgressive hybridization with feral domestic cats (Felis silvestris catus). Over the last decade, the genotyping of highly polymorphic molecular markers (specifically microsatellites, short tandem repeats) and partial mitochondrial DNA sequences, combined with new Bayesian statistical tools, have radically improved the knowledge on wildcat population genetics and admixture with the domestic cat (for example, Beaumont et al, 2001;Randi et al, 2001;Pierpaoli et al, 2003;Kitchener et al, 2005;Lecis et al, 2006;Oliveira et al, 2008a, b;O'Brien et al, 2009;Hertwig et al, 2009;Eckert et al, 2010;Mattucci et al, 2013). Wildcats have been domesticated from African wildcat (F.s.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, observations of wild cat cubs Felis silvestris Schreber, 1777 emphasize the importance of conservation strategies to be applied because the presence of feral domestic cats may represent a threat for the wild genome (cf. Randi et al 2001). The presence of pine marten Martes martes (Linnaeus, 1758) ( Figure 3) at a relatively high frequency of observation could be due to a recent range expansion of this species, maybe helped by the human abandonment of the countryside and by the progressive advance of woodlands, the elective habitat of this species (Balestrieri et al 2010).…”
Section: Carnivores Of Conservation Interestmentioning
confidence: 99%